Lack of Computer Programs Slows Use, Humanists Say. - Desruisseaux, Paul (Chronicle of Higher Education, 1983)
Focuses on the role of the lack of computer programs in the failure of U.S. college and universities to utilize computers as a teaching aid and include computer-aided instruction in the undergraduate curriculum discussed at a meeting held in New York. Significance of the growth of high technology to the capabilities of computers; Emphasis of courseware manufacturers on products for elementary and secondary school instruction; Interest of companies in investing in courseware for undergraduate curriculum.